Government Expenditure Arrears Accumulation During the COVID-19 Period : An Update - Lacey, Eric; Massad, Joseph; Mastruzzi, Massimo; Utz, Robert (World Bank, Washington, DC, 2021)
Economic shocks and crises typically lead to a sharp increase in government expenditure arrears with corrosive effects on the economy. In order to assess the evolution of government expenditure arrears during the Coronavirus (COVID-19) crisis, the World Bank collected information on public expenditure arrears in client countries in June 2020. The results of this initial data collection exercise are reported in an MTI Insight Note (An Overview of the Potential Impact of the Coronavirus (COVID-19) Crisis on the Accumulation of government Expenditure Arrears), which also discusses the definition of government expenditure arrears, measurement and reporting issues, the main drivers and economic consequences of arrears accumulation, and options for preventing and managing arrears accumulation. This note presents an update based on information available by February 2021.